TEACHERS’ CHALLENGES IN TEACHING CHILDREN WITH SPECIAL NEEDS IN PUBLIC KINDERGARTEN CLASSROOMS - Ni Made Yuniari; Susila, Komang Dedik (Widya Balina, 2025)
Inclusive education in early childhood settings emphasizes equal learning opportunities for children with special needs within regular classrooms. However, the implementation of inclusive practices in public kindergarten classrooms presents various challenges for teachers, particularly due to diverse learner needs and limited institutional support. This study aims to explore the challenges faced by teachers in teaching children with special needs in public kindergarten classrooms. Employing a qualitative descriptive research design, the study was conducted in a public kindergarten that implements inclusive education. The participants were kindergarten teachers selected through purposive sampling based on their direct experience teaching children with special needs. Data were collected through semi-structured interviews and classroom observations, and were analyzed thematically to identify recurring patterns and issues. The findings indicate that teachers encounter significant challenges in managing children’s behavior and attention, implementing instructional adaptations without systematic planning, assessing inconsistent developmental progress, and coping with emotional stress. These challenges are further intensified by limited professional competence, lack of formal training in inclusive education, and minimal institutional support, including the absence of support teachers and specialist services. The study highlights the need for targeted professional development, structured instructional planning, and strengthened school support systems to ensure the effective and sustainable implementation of inclusive education in public kindergarten settings.